Tradisi Sayyang Pattu'du di Mandar (Studi Kasus Desa Lapeo) - Ruhiyat, Ruhiyat (Jurnal Studi Agama dan Masyarakat, 2017)
In the sociological view, Mandarese believes that Sayyang Pattu‟du‟ tradition has a close affinity with each other. As a reason, Pattu'du‟ Sayyang tradition was held in order to appreciate the children who have finished readying all the content of their Al-Qur‟an. For the resident of Mandar especially in Lapeo village, the Tradition of Sayyang Pattu'du‟ meant as a socialization tool because involve the resident in